2018
DOI: 10.1016/j.artd.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the period of greatest blood loss after lower limb arthroplasty

Abstract: BackgroundThe use of tranexamic acid (TXA) in total hip replacement (THR) typically reduces blood loss by approximately 400 mL, and typical total blood loss is still approximately 1 L. A barrier to harnessing the full potential of TXA is disagreement on the optimum timing of administration. To address this, we aimed to identify the period of greatest blood loss.MethodsWe analyzed the perioperative data of 870 patients who had undergone THR, total knee replacement, or unicompartmental knee replacement just befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…The rate of blood transfusion within this cohort was much higher than would be expected today with 38% of patients requiring at least 1 unit of packed red cells postoperatively. Comparatively, a recent publication by Magill et al [30] in 2018 revealed a transfusion rate of 12.5% in 393 patients undergoing THA under the care of the senior author. It is important to note that the rate of transfusion after THA was historically much higher over the past decade than that in the present day.…”
Section: Current Controversies and Future Considerationsmentioning
confidence: 98%
“…The rate of blood transfusion within this cohort was much higher than would be expected today with 38% of patients requiring at least 1 unit of packed red cells postoperatively. Comparatively, a recent publication by Magill et al [30] in 2018 revealed a transfusion rate of 12.5% in 393 patients undergoing THA under the care of the senior author. It is important to note that the rate of transfusion after THA was historically much higher over the past decade than that in the present day.…”
Section: Current Controversies and Future Considerationsmentioning
confidence: 98%
“…In contrast, in another large series, knee arthroplasty has been shown to be associated with higher volume of blood loss . While tourniquet use is expected to decrease the amount of bleeding in knee surgery, in fact, 90% of the bleeding in the perioperative period has been shown to be between the skin closure and the postoperative first day . Therefore, we think that the presence of a joint capsule that restricts bleeding in the knee, or the incision made between large muscle groups in the hip joint, potentially influences the amount of blood.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were encouraged to move the surgical limb immediately and formal physiotherapy-led rehabilitation was commenced on the first post-operative day up until and including the discharge day. Blood loss was estimated using the following method [ 17 ]:…”
Section: Methodsmentioning
confidence: 99%